Histopathological Overview of Kidney Given Extract of Thistle Leaf (Calotropis gigantea) and Aspirin® Inducted to White Rats (Rattus norvegicus) - Joharry Leto Bele, Alexander (Journal of Basic Medical Veterinary, 2022)
This research aimed to determine the overview of gastric histopathology that contained necrosis, degeneration and inflamed-cell infiltration in gastric muccose that inducted by aspirin and widuri leaves (Calotropis gigantean) ekstract in white rat (Rattus norvegicus). The experimental animals that used in this research were 25 white rats that selected by simple random sampling technic. The design that used in this research was complete random design that devided into 5 groups of treatment and 5 repetition in each groups. The treatment group were P0 = negative control group, P1 = positive control group that gave aspirin 500 mg/kg body weight, P2 = was the group that given aspirin 500 mg/kg body weight and widuri leaves extract 50 mg/kg body weight, P3 = was the group that given aspirin 500 mg/kg body weight and widuri leaves extract 100 mg/kg body weight, P4 = was the group that given aspirin 500 mg/kg body weight and widuri leaves extract 150 mg/kg body weight. Data that collected analyzed by Kruskal-Wallis statistic test and Mann- Whitney Test. Based on the by Kruskal-Wallis Test and Mann-Whitney Test, p (Asymp.sig) < 0.05. That means there was the real different between groups of treatments. The conclusion of this research was the dosis 100 mg/kg body weight dan 150 mg/kg body weight dose of widuri leaves extract could decrease the gastric necrosis, degeneration and inflammation.